2021
DOI: 10.13102/sociobiology.v68i2.6071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat Conversion on Ant Functional Groups: A Global Review

Abstract: Conversion of natural to anthropogenic environments affects biodiversity, and the understanding of these impacts may be improved by assessing how different functional groups respond to such land conversion. We studied land conversion impacts on ant functional groups, as ants are ecologically important and respond well to various environmental changes. We hypothesized that conversion of natural to anthropogenic environments modifies the composition of functional groups, fostering generalist and opportunistic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 103 publications
0
4
0
3
Order By: Relevance
“…Susilawati and Indriati (2020) also found that Dolichoderus ants were the most abundant in coffee plantations in Indonesia. Dolichoderus ants were included in the dominant Dolichoderinae ant functional group because of their dominant behavior (Santos et al 2021). Meanwhile, Pheidole ants were the dominant ground ants in coffee plantations (Ennis and Philpott 2017).…”
Section: Ant Communities In Coffee Agroforestry Systems In East Javamentioning
confidence: 99%
See 1 more Smart Citation
“…Susilawati and Indriati (2020) also found that Dolichoderus ants were the most abundant in coffee plantations in Indonesia. Dolichoderus ants were included in the dominant Dolichoderinae ant functional group because of their dominant behavior (Santos et al 2021). Meanwhile, Pheidole ants were the dominant ground ants in coffee plantations (Ennis and Philpott 2017).…”
Section: Ant Communities In Coffee Agroforestry Systems In East Javamentioning
confidence: 99%
“…Ants are very sensitive to environmental change. Agriculture intensification, human disturbance, and land conversion are known to affect ant diversity (Solar et al 2016;Rizali et al 2020;Santos et al 2021). Because of their sensitive and rapid responses, ants can become good indicators of change in the environment (Tiede et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of natural and complex landscapes into ant anthropized environments, have led to the simplification, loss and fragmentation of native habitats. 1 In general, habitat disturbances such as urbanization affect ant communities directly, by reducing the availability of resources and removing colonies, and indirectly, through changes in habitat structure, nesting site availability, temperature and humidity. 2,3 The impacts of habitat conversion on fungus-growers probably occurred because some land uses, with intensive management, in addition to homogenizing the habitat, strongly affect ant fauna, 4,5 especially leaf-cutting ants.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of natural and complex landscapes into ant anthropized environments, have led to the simplification, loss and fragmentation of native habitats 1 . In general, habitat disturbances such as urbanization affect ant communities directly, by reducing the availability of resources and removing colonies, and indirectly, through changes in habitat structure, nesting site availability, temperature and humidity 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, os efeitos da fragmentação de habitat sobre as formigas variam entre diferentes grupos funcionais (Santos et al 2021). As formigas arbóreas, por exemplo, são afetadas pelos efeitos da fragmentação (Lozano-Zambrano et al 2009, Rocha-Ortega & Coronel-Arellano 2019 enquanto que as formigas de solo são geralmente mais afetadas por características ambientais locais como, por exemplo, a porcentagem de cobertura do dossel e a composição e porcentagem de argila no solo (Debuse et al 2007, Rocha-Ortega & Coronel-Arellano 2019.…”
Section: Introductionunclassified